L’arbre fruitier en Avesnois : le « passeur de mémoires » (xive-xxie siècle) - Marie Delcourte (Projets de Paysage)
Nowadays, trees are increasingly considered as part of a cultural heritage which needs to be identified and protected, this is the case of fruit trees in the region of Avesnes in the North of France. For centuries, the fruit tree has been the focus of much attention because it contributes greatly to the identity of the landscape and is a source of income the importance of which has varied over time. This relationship between people and fruit trees is reflected in the way the tree forms a part of the landscape. This article, which presents the initial findings of an ongoing research project, seeks to analyse the relation between people and trees through time.